Pembelajaran Project Based On Alquran (PBQ) dalam Penguatan Profil Pelajar Pancasila dan Kompetensi Kognitif Pada Materi IPA - Muhamad Jalil; Ahmad Hamdani Hasanuddin; Alpidalpita Alpidalpita (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2024)
The aim of this research is to explain the PBQ learning steps in grade IV science material and determine the effectiveness of the PBQ model on students’ cognitive learning outcomes and P5 profiles. This research is quantitative research with pre-experimental designs. Data in the form of PBQ steps, cognitive learning outcomes, and P5 character. The data analysis technique uses the paired t test and descriptive percentages. The research results show that implementing learning using the PBQ model on science material consists of four steps, namely problem determination, research study, research activities, and reporting. The application of PBQ learning is effective on cognitive competence as an indicator of P5 because t count > t table (3.045 > 2.069), then Ho is rejected. Achieving the character of Strengthening the Pancasila Student Profile in SD/MI science material received a score of 81.44074 (good) which has exceeded the KKTP 75. The indicators for each dimension P5 in the dimension of having faith, being devoted to God Almighty (YME), and having noble morals received a score 82.72%, global diversity (83.95%), mutual cooperation (76.54%), and independence (82.72%).